MANAJEMEN KEAMANAN INFORMASI UNTUK TRANSFORMASI DIGITAL INSURCO BERBASIS COBIT 2019 FOCUS AREA INFORMATION SECURITY - Andyas, Muhammad Anugerah; Mulyana, Rahmat; Nurtrisha, Widyatasya Agustika (Universitas Lancang Kuning, 2023)
Previous research has shown the contribution of IT governance to digital transformation. However, further exploration is needed regarding the role of information security management in overseeing such changes through a case study of InsurCo insurance company. This is necessary in line with the latest guidance provided by PER-2/MBU/03/2023 on corporate governance and the Indonesian Financial Services Sector Master Plan 2021–2025 regarding the acceleration of digital transformation. This research method utilizes Design Science Research based on interview data. DSS05 Managed Security Service, APO13 Managed Security, and APO12 Managed Risk were selected as the priority implementation areas of the COBIT 2019 Information Security Focus Area. Capability assessments, gap analysis, recommendation development, solution design, and roadmap have been conducted on the seven related governance components. An estimated average maturity improvement of 0,8 (30,77%) was observed in these three processes. This study contributes to the knowledge base on the concept of prioritizing information security management to support organizational digital transformation, and it is particularly beneficial for InsurCo in ensuring the success of its strategic programs, as well as for the insurance industry in general.